Co-disciplinary Physics and Mathematics Research and Study Course (RSC) within three study groups: teachers-in-training, secondary school students and researchers - Otero, Maria Rita (2016)
This work shows the results of a research carried out in secondary school and university developing a co-disciplinary Research and Study Course (RSC) on questions connected to Physics and Mathematics in different groups. We present preliminary results of the RSC developed in three different groups: science education researchers, N=25 Mathematics teacher students (training teachers of Mathematics) at University, and N= 68 secondary school students. The development and scope of the RSC in each group is described by using the RSC components as defined by Chevallard?s Anthropological Theory of the Didactic (ATD) (2012). Furthermore, a short description of the Praxeological Model of Reference is presented. This model was built by the researchers group in order to reply to the generative question, unknown in the beginning, and to anticipate and to conceive the evolution of the possible SRC in each institution. Some general results in each group are discussed and some conclusions concerning the ecology of the pedagogy of research and questioning the world at university and secondary schools are drawn.